Nilai pH dan Organoleptik Daging Domba dengan Perendaman Menggunakan Bawang Batak (Allium chinense G. Don) dan Daun Jambu Biji (Psidium guajava L.) - Nur Asmaq; Fachrina Wibowo; Muhammad Rinaldi (Peternakan Lokal, 2023)
Batak onions (Allium chinense G. Don) and guava leaves (Psidium guajava L.) are plants that are commonly found in North Sumatra Province. Batak onion is an endemic plant and only found in this province. The antioxidant content in these two plants can be used as a natural preservative for lamb meat. This study aims to see the effect of Batak onion (Allium chinense G. Don.) and guava leaf (Psidium guajva L.) extracts on the pH and organoleptic values ​​of lamb meat. The method used in this study was an experimental method with 4 treatments and 5 replications in a completely randomized design. The results of the study showed that there was a nonsignificant (P>0,05) effect on the pH value. The organoleptic value had a dark color, the aroma changed like the aroma of the extract and the texture was chewy.